2014
DOI: 10.1002/lpor.201300163
|View full text |Cite
|
Sign up to set email alerts
|

On the role of shot noise in carrier‐envelope phase stabilization

Abstract: This paper represents a systematic investigation of detection shot noise in carrier-envelope phase (CEP) stabilization. Numerical simulations are conducted to calculate the influence of shot noise in laser oscillators. These results are compared with experimental results for Ti:sapphire lasers. It is found that shot noise imposes a limitation for obtaining sub-100 mrad CEP jitters. Careful interferometer design is necessary to push this limit toward 10 mrad. In contrast to oscillator stabilization, shot noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
7
0
5
Order By: Relevance
“…We are aware of only a single published OOL measurement of Er:fiber combs [10]. At high frequencies above ∼10 kHz, OOL measurements are dominated by a white noise background that stems from the detection of shot noise [5]. After carefully optimizing the beat note signalto-noise ratio, one can obtain shot noise limitations down to about S CEP ϕ f 10 −6 rad∕ Hz p…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…We are aware of only a single published OOL measurement of Er:fiber combs [10]. At high frequencies above ∼10 kHz, OOL measurements are dominated by a white noise background that stems from the detection of shot noise [5]. After carefully optimizing the beat note signalto-noise ratio, one can obtain shot noise limitations down to about S CEP ϕ f 10 −6 rad∕ Hz p…”
mentioning
confidence: 98%
“…A number of authors have already identified various noise contributions to the residual CEP jitter [2,[5][6][7][8][9]. These measurements rely on a spectral analysis of the phase noise measured in an out-of-loop (OOL) interferometer, which is not directly involved in the stabilization of the CEP.…”
mentioning
confidence: 99%
“…4 also shows the signal that is obtained when the interference is disabled by inserting a glass plate into the beam path of the f − 2f interferometer. The observed visibility of the beat note indicates that residual phase jitters well below 100 mrad are possible [16].…”
mentioning
confidence: 89%
“…If the latter were true, one would expect to see a structured noise spectrum rather than a flat plateau. In particular, the practical absence of line frequency harmonics implies that we are actually seeing the limitations of the oscillator stabilization here [16]. In any case, it appears challenging to reduce this broadband 230 mrad noise signature with the traditional slow spectral interferometry approach [12] typically employed for amplifier stabilization.…”
mentioning
confidence: 99%
“…Ennek eredményeként az ultrarövid impulzusok CEP-jének detektálása és stabilizálása a lézeroszcillátorokkal és CPA rendszerekkel elérhető impulzusidő lerövidülésével egyre fontosabbá vált a 2000-es évek elején. Több kísérleti elrendezést is kifejlesztettek az elmúlt két évtizedben a CEP mérésére [128]. A CEP csúszásának, azaz az offszet frekvencia változásának megmérésére egy femtoszekundumos oszcillátor esetén elsőként egy nemlineáris keresztkorrelációs technikát alkalmaztak, amelyhez egy kellően nagy karhosszal rendelkező interferométert valósítottak meg [129].…”
Section: Ii3 Vivő-burkoló Fázis Mérése éS Stabilizálásaunclassified